2011
DOI: 10.1093/ndt/gfr264
|View full text |Cite
|
Sign up to set email alerts
|

Renal transplant recipients have elevated frequencies of circulating myeloid-derived suppressor cells

Abstract: RTRs, CKD patients and ICI-SCC(Pos) have increased MDSC frequencies and MDSC/DC ratios. These changes may impact on cancer immunosurveillance. Therefore, MDSC represent both a potential therapeutic target and prognostic marker in these patients, with respect to the development of SCC and other malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 37 publications
3
49
1
Order By: Relevance
“…Another clinical investigation found that elevated frequencies of circulating CD14− and CD14+ MDSCs were found in the recipients of renal transplants. Furthermore, CD14− MDSCs were found to be associated with higher occurrence of squamous cell carcinoma in these patients [41]. …”
Section: Induction Of Transplant Tolerance By Mdscsmentioning
confidence: 99%
“…Another clinical investigation found that elevated frequencies of circulating CD14− and CD14+ MDSCs were found in the recipients of renal transplants. Furthermore, CD14− MDSCs were found to be associated with higher occurrence of squamous cell carcinoma in these patients [41]. …”
Section: Induction Of Transplant Tolerance By Mdscsmentioning
confidence: 99%
“…Many of these investigations have concentrated on the adaptive response to alloantigen that is generated by T cells, though significant attention has also been focused on other leukocyte subsets including NK cells, dendritic cells (DCs), regulatory T cells (Treg), myeloid derived suppressor cells (MDSCs), regulatory macrophages (Mregs) and other suppressor cell subsets (Geissler, 2012; Hock et al, 2012; Hutchinson et al, 2011; Jungraithmayr et al, 2013; Krystufkova et al, 2012; Lees et al, 2011; Loewendorf & Csete, 2013; Mazariegos et al, 2003; Riquelme et al, 2013; Villard, 2011; Wood et al, 2012). …”
Section: Monitoring Regulatory Cells and Other Immune Cell Subsetsmentioning
confidence: 99%
“…Shortly after transplantation they migrated from the bone marrow to the transplant where they participated in the induction of Treg and prevented initiation of adaptive immune responses (Garcia et al, 2010). Lastly, elevated frequencies of circulating CD14 Neg and CD14 Pos MDSC have recently been recorded in patients recipients of renal transplants and CD14 Neg MDSC were found associated with occurrence of squamous cell carcinoma in these patients (Hock et al, 2012). Thus MDSC has potential functional relevance in kidney graft recipients with respect to transplant tolerance but also cancer immunosurveillance.…”
Section: Mdsc and Transplantationmentioning
confidence: 99%
“…In addition to their recognized role in tumor tolerance, they potentially exert a role in the induction and maintenance of transplant tolerance. However, whether MDSC generated post-transplantation result from creeping inflammation and interferes with immunosurveillance or potentially constitute an appropriate immune regulatory response, as recently explored (Hock et al, 2012), remains to be established. Further phenotyping MDSC post-transplantation in humans might help deciphering their potential “physiological” role and understanding whether, in spite of their non-specific immunosuppressive activity, they might be used in cell therapies in synergy with existing immunosuppressive therapies.…”
Section: Mdsc and Transplantationmentioning
confidence: 99%